Time Variation of Ex‐Dividend Day Stock Returns and Corporate Dividend Capture: A Reexamination - Naranjo, Andy; Nimalendran, M.; Ryngaert, Mike (Journal of Finance, 2000)
This paper documents some empirical facts about ex‐day abnormal returns to high dividend yield stocks that are potentially subject to corporate dividend capture. We find that average abnormal ex‐dividend day returns are uniformly negative in each year after the introduction of negotiated commission rates and that time variation in ex‐day returns during the negotiated commission rates era is consistent with corporate tax‐based dividend capture. Ex‐day returns are more negative when the tax advantage to corporate dividend capture is greatest and more positive when increases in transaction costs and risk reduce incentives to engage in corporate tax‐based dividend capture.